Basics of the construction of an official discourse of consensus on international migration in South America - González Zepeda, Carlos Alberto; Culebro Moreno, Jorge Enrique (Universidad Autónoma del Estado de México, 2017)
The article shows progress in building a regional official discourse on migration in South America, which occurs in the midst of complex processes, where multiple actors are engaged with the South American Conference on Migration as an axis. It also shows the principles and objectives that guide the construction and seek to homogenize migration policies, forming an international block on the issue, and eventually consolidate broader strategic visions.